2016
DOI: 10.1158/2159-8290.cd-15-0023
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vessels, Inflammation, and Immunity in Skin Cancer

Abstract: Skin is a highly ordered immune organ that coordinates rapid responses to external insult while maintaining self-tolerance. In healthy tissue, lymphatic vessels drain fluid and coordinate local immune responses; however, environmental factors induce lymphatic vessel dysfunction, leading to lymph stasis and perturbed regional immunity. These same environmental factors drive the formation of local malignancies, which are also influenced by local inflammation. Herein, we discuss clinical and experimental evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 151 publications
4
59
0
3
Order By: Relevance
“…We have previously reported that blood and lymphatic vessel density is increased in the scalp compared to torso and extremity, as indicated by CD31 and D2-40 staining, respectively [20]. Although correlations between lymphatic density and melanoma metastasis has been reported [21], the issue remains controversial [22] and a histological study of scalp melanomas found high rates of both vascular and lymphatic invasion [23]. In addition, Hung et al[24] observed angiotropism in 14/20 primary tumors that developed BM.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that blood and lymphatic vessel density is increased in the scalp compared to torso and extremity, as indicated by CD31 and D2-40 staining, respectively [20]. Although correlations between lymphatic density and melanoma metastasis has been reported [21], the issue remains controversial [22] and a histological study of scalp melanomas found high rates of both vascular and lymphatic invasion [23]. In addition, Hung et al[24] observed angiotropism in 14/20 primary tumors that developed BM.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that as many as 20% of cancers are instigated by chronic inflammation or persistent infections (115). Inflammatory cytokines and cells are implicated in tumorigenesis and tumor progression in most sites, and have been extensively documented in cancers of the stomach (116, 118), colon (16, 35, 63), skin (3, 65, 78, 126, 128), liver (4, 8, 41), breast (2, 21, 48), lung (32, 83, 100), and head/neck (12, 14, 15). …”
Section: The Role Of Inflammation In Cancer Initiationmentioning
confidence: 99%
“…The abundant clinical and experimental evidence correlating lymphangiogenesis with tumor progression contrasts with reports that lymphangiogenesis in tissue transplantation can promote graft rejection (18), and further confounding the issue are reports suggesting that lymphangiogenesis promotes immune resolution in chronic inflammation (12,13). Therefore, it is likely that lymphatic vessels may serve multiple and complex roles in both the induction and resolution of local immune responses in acute versus chronic inflammation (19).…”
Section: Introductionmentioning
confidence: 99%